Motivação para leitura em alunos do 6º ano do ensino fundamental: análise por dimensões, rendimento, sexo e escola - Torezan, Keila Roberta (Universidade Federal de São Carlos, 2012)
In Brazil, many data indicate the school difficulties found by the students, mainly in the public teaching. The analysis of the motivational factors has shown a promising alternative to the understanding of the low academic achievement. Motivation can be understood as a variety of psychological processes that lead to a choice, stimulate and begin a behavior directed toward a goal, which guarantee the permanence on it. Researches have focused the effects of the students motivation for reading on the academic achievement. This study focused on the characterization of students eleven dimensions of the motivation for reading. Among the dimensions intrinsic and extrinsic motivation for reading, self-efficacy and social aspects were included. Important aspects related to the students to understand the low engagement in reading activities for a considerable amount of Brazilian students were examined. The proposal is based on the founds between the relation of the students reading motivation quality and their involvement with the reading. The descriptive study searched to: 1) characterize the dimensions of motivation for reading (self-efficacy, intrinsic and extrinsic motivation and social proposals) of a group of 6th grade students in function of their reading achievement, of the gender and the location of the school attended by the students; 2) identify if there s difference in the motivation for reading among the students with low media and high grades in reading, between boys and girls and between the students attending different schools located in the central area and in the suburbs of a medium city. 119 students participated of this study, 61 were from the central school which 25 were boys and 36 were girls and 58 from the suburb school which 33 were boys and 25 were girls, the average age of the participants was 10 years and 7 months old. Were used as instruments: one scale to evaluate the dimensions for reading composed by 54 items developed to measure each dimension for reading Motivation Reading Questionnaire - and the students grades in reading on the first school semester of 2011. To analyze the data, statistics tests were done. They detected that the motivation for reading is multidimensional. The results of this present study corroborate the discoveries of the literature of reading motivation that points out difference between boys and girls, among students with different academic achievement and also difference between the students from the different schools location. The girls, the students from the central school and the students with medium and high academic achievement showed motivation reading aspects more positive related to boys, than students with low academic achievement and the students attending the suburb school.
Keywords: Educação especial; Motivação para leitura; Leitura; Motivação; Reading; Motivation; Reading Motivation; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL